HISTORICAL BACKGROUND OF TERRORISM IN JAMMU AND KASHMIR IN INDIAN POLITICS - Reetu Gupta, Dr. Pratima Bhardwaj (Chelonian Research Foundation, 2023)
The Jammu and Kashmir dispute between India and Pakistan is a unique example of how the actual state terrorism by one side is being camouflaged under the guise of an intense propaganda campaign, which dubs the other side as a terrorist state. India accuses Pakistan of sponsoring terrorism in Indian-held Kashmir. Yet it is the Indian government, which has adopted repressive policies to subdue the Kashmiri people struggle for Azadi in the held-state under its control. Though more manifest in the context of the Jammu and Kashmir state, in other Indian states, too there are similar charges against the Indian Centre, by a variety of popular movements fighting for their rights. The Independence of India from the British Empire was marked by its partition into two countries. As a corollary to Independence and partition of India, 500-odd princely state which had direct relationship with the British Empire was required to integrate with either India or Pakistan. The process of integration of princely state was not without its highs and lows. Some of the princely states like Hyderabad, Junagarh and Jammu and Kashmir, posted quite a few problems at the time of integration for several reasons, namely the inclination of its rulers, the religious component of the local population and the competing interests of the two successor states, India and Pakistan. Hyderabad and Junagarh were favorably resolved in India’s favour. Integration of Jammu and Kashmir with India was not a smooth affair. It was only after Pakistan-aided forces including the Pakistan army had invaded Jammu and Kashmir then the ruler of Jammu and Kashmir signed the instrument of succession in India’s favour. The salvage operation of throwing the Pakistan-aided forces and military out of Jammu and Kashmir could not be accomplished fully, because India agreed that the United Nations, to which the Kashmir dispute was to be referred, would help in the resolution of the Kashmir issue within the accepted legal framework which was in India’s favour. However, India’s experience with the United Nations was a great disappointment. KEYWORDS: Terrorism, Corollary, Princely State, Accomplished, United Nations, British Empire, Integration.